China's Anti‐Corruption Campaign and Financial Reporting Quality - Hope, Ole‐Kristian; Yue, Heng; Zhong, Qinlin (Contemporary Accounting Research, 2020)
ABSTRACT We examine the impact of China's anti‐corruption campaign on firm‐level financial reporting quality (FRQ). As an important component of the anti‐corruption campaign, in October 2013, “Rule 18” was issued to prohibit party and government officials from serving as directors for publicly listed firms. The regulation led to a large number of official directors resigning from their roles as directors involuntarily. As such, Rule 18 has effectively weakened, if not fully discontinued, the political connections of the firms that previously hired officials as directors. Our empirical analyses employ a difference‐in‐differences research design with firm fixed effects and propensity‐score matching to examine the pre‐ and post‐period FRQ around the enactment of Rule 18. We find that, compared to propensity‐score‐matched control firms, FRQ of firms with resigned official directors increases after Rule 18. Further evidence suggests that the impact is stronger when firms are located in regions with more developed financial markets and in regions with higher judiciary efficiency. We also find that the effect is more pronounced when firms are non‐state‐owned, received preferential credits, and face refinancing pressure.